An alternative explanation of PMSE-like scatter in MF radar data - Jones, G. O. L.; Clilverd, M. A.; Espy, P. J.; Chew, S.; Fritts, D. C.; Riggin, D. M. (CCSD, 2004)
International audience There have been reports in the literature that spaced-antenna MF radars may provide a source of data on Polar Mesospheric Summer Echoes (PMSE). Even though the expected scatter from PMSE at MF frequencies is very much weaker than at VHF, the wide distribution of sites and long duration of data sets for MF radar systems could provide valuable information about the occurrence of PMSE. This paper tests whether there is any evidence of PMSE in the profiles derived using the MF radar at Rothera, Antarctica, one of the few such radars at high southern latitudes. Over a year of data during 1997/1998 has been analysed for the occurrence of persistent features around midday in the altitude range 60-95km. Criteria were chosen to test the likelihood that some of the narrow peaks in the power profiles were manifestations of electron density structures associated with PMSE. Although a small number of persistent features were seen at altitudes of 80-85km that are typically associated with PMSE, there was no seasonality in their occurrence. A detailed analysis of specific days showed that two peaks were often seen with altitude separations consistent with the vertical wavelength of the diurnal tide. Persistent features were also detected at altitudes of 70km and 90km during the winter months, thus showing a quite different seasonality to that of PMSE. An estimate of the turbulence caused by the breaking of gravity waves that have propagated up from the lower atmosphere shows that at Rothera significant energy is deposited near 80km during summer, and near 70 and 90km during winter. This seasonal variability is driven by the screening effect of stratospheric winds, and it appears that breaking gravity wave dynamics, rather than PMSE phenomena, can explain many of the localised altitude features in the MF radar data.